2015
DOI: 10.4103/1735-9066.161013
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in pregnancy and postpartum in women with mild and severe preeclampsia

Abstract: Background:Risk for anxiety and depression is increased in women with high-risk pregnancy. The aim of this study was to evaluate anxiety and depression in women with mild and severe preeclampsia at admission and 6 weeks postpartum.Materials and Methods:In this cohort study, 122 preeclamptic women who were admitted to the Public hospital and Tamin Ejtemaee hospital of Mashhad were included. Selection was done by convenience sampling method. Beck Depression Inventory II (BDI-II) and Spielberger State-Trait Anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
(29 reference statements)
2
30
0
4
Order By: Relevance
“…The indices for depression (31, 249, 250) and anxiety (31, 38, 249) are elevated in PE, while the frequency of PTSD is increased for several years after the index pregnancy (3742). One clinical study observed that the risk for postpartum depression was associated not to the severity of PE, but rather to its consequences (e.g., perinatal death), even after adjusting for the confounding variables of age, ethnicity, and educational level of the mother (250).…”
Section: Cerebrovascular and Higher Function Neurological Consequencementioning
confidence: 99%
See 2 more Smart Citations
“…The indices for depression (31, 249, 250) and anxiety (31, 38, 249) are elevated in PE, while the frequency of PTSD is increased for several years after the index pregnancy (3742). One clinical study observed that the risk for postpartum depression was associated not to the severity of PE, but rather to its consequences (e.g., perinatal death), even after adjusting for the confounding variables of age, ethnicity, and educational level of the mother (250).…”
Section: Cerebrovascular and Higher Function Neurological Consequencementioning
confidence: 99%
“…While resilience shielding against psychological stress (251) and psychotherapeutic treatment (252) can attenuate the duration of the episode, a previous history of depression coupled with experiencing a preeclamptic index pregnancy can significantly contribute to the onset of PTSD and exacerbate the anxiety of planning future pregnancies (39). The deleterious effects of prenatal maternal psychosocial stressors on fetal development are well documented, where increased incidences of maternal depression (3436) and anxiety (3133) are significantly correlated to low fetal birth weight, IUGR, and premature birth (3236, 38). …”
Section: Cerebrovascular and Higher Function Neurological Consequencementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the complications of pregnancy were related to maternal stress during pregnancy2425, and air pollution was associated with the development of complications of pregnancy26. However, the modifying effects of complications of pregnancy on the association between air pollution and maternal stress during pregnancy remain unclear2728.…”
mentioning
confidence: 99%
“…Numerous factors that influence a pregnancy and its subsequent outcome have been identified, including illness (Atta et al, 2016;Ellington et al, 2011;Guntupalli, Hall, Karnad, Bandi, & Belfort, 2015;Hartert et al, 2003;Lapinsky, 2010;Mouyis, Thornton, Williams, & Giles, 2017;O'Brien et al, 2014), stress (Carmichael & Shaw, 2000;Christian, 2014;Coussons-Read, Okun, & Nettles, 2007;Davis, Glynn, Waffarn, & Sandman, 2011;Livingston, Otado, & Warren, 2003;Rini, Dunkel-Schetter, Wadhwa, & Sandman, 1999;Sandman, Wadhwa, Chicz-Demet, Dunkel-Schetter, & Porto, 1997), emotional states such as depression and anxiety (Abedian, Soltani, Mokhber, & Esmaily, 2015;Diego et al, 2004;Lewis, Austin, Knapp, Vaiano, & Galbally, 2015;Orr, James, & Blackmore, 2002), and disturbed sleep (Lee, 2006;Okun, Hall, & Coussons-Read, 2007;Okun, Hanusa, Hall, & Wisner, 2009;Okun, Schetter, & Glynn, 2011;Tomfohr, Buliga, Letourneau, Campbell, & Giesbrecht, 2015). While there is an extensive literature about the immunological consequences of illness, stress, and psychopathology during gestation (Christian, 2014;Christian, Franco, Iams, Sheridan, & Glaser, 2010;Corwin & Pajer, 2008;Coussons-Read et al, 2007;Madan et al, 2009;Maes et al, 2000;Spradley, Palei, & Granger, 2015), little is known regarding the effects of chronic or persistent sleep loss/disruption during pregnancy and its impact on immune dysregulation that may impact maternal and fetal health and pregnancy outcomes.…”
mentioning
confidence: 99%